The S100A10 Pathway Mediates an Occult Hyperfibrinolytic Subtype in Trauma Patients. Issue 6 (June 2019) - Gall, Lewis S.; Vulliamy, Paul; Gillespie, Scarlett; Jones, Timothy F.; Pierre, Rochelle S. J.; Breukers, Sabine E.; Gaarder, Christine; Juffermans, Nicole P.; Maegele, Marc; Stensballe, Jakob; Johansson, Pär I.; Davenport, Ross A.; et al.
Abstract : Objective: To determine the characteristics of trauma patients with low levels of fibrinolysis as detected by viscoelastic hemostatic assay (VHA) and explore the underlying mechanisms of this subtype. Background: Hyperfibrinolysis is a central component of acute traumatic coagulopathy but a group of patients present with low levels of VHA-detected fibrinolysis. There is concern that these patients may be at risk of thrombosis if empirically administered an antifibrinolytic agent. Methods: A prospective multicenter observational cohort study was conducted at 5 European major trauma centers. Blood was drawn on arrival, within 2 hours of injury, for VHA (rotation thromboelastometry [ROTEM]) and fibrinolysis plasma protein analysis including the fibrinolytic mediator S100A10. An outcomes-based threshold for ROTEM hypofibrinolysis was determined and patients grouped by this and by D-dimer (DD) levels. Results: Nine hundred fourteen patients were included in the study. The VHA maximum lysis (ML) lower threshold was determined to be <5%. Heterogeneity existed among patients with low ML, with survivors sharing similar clinical and injury characteristics to patients with normal ML values (5–15%). Those who died were critically injured with a preponderance of traumatic brain injury and had a 7-fold higher DD level (died vs. survived: 103, 170 vs. 13, 672 ng/mL, P < 0.001). Patients with low ML and high DD demonstrated a hyperfibrinolytic biomarker profile, low tissue plasminogen activator levels but high plasma levels of S100A10. S100A10 was negatively correlated with %ML (r = −0.26, P < 0.001) and caused a significant reduction in %ML when added to whole blood ex-vivo. Conclusions: Patients presenting with low ML and low DD levels have low injury severity and normal outcomes. Conversely, patients with low ML but high DD levels are severely injured, functionally coagulopathic and have poor clinical outcomes. These patients have low tissue plasminogen activator levels and are not detectable by ROTEM. S100A10 is a cell surface plasminogen receptor which may drive the hyperfibrinolysis in these patients and which when shed artificially lowers %ML ex-vivo. Abstract : Supplemental Digital Content is available in the text